A rare presentation of craniopharyngioma: Delayed puberty - Inci, Mehmet Fatih; Özkan, Fuat; Bozkurt, Selim; Demir, Caner Feyzi (BMJ Publishing Group, 2012)
Craniopharyngiomas are the most frequently encountered suprasellar tumours in children. Owing to the slow growth rate of these tumours, they are often quite large before becoming symptomatic. They are more common among children and older adults (55-74 years). Depending upon the direction of growth and tumour size, craniopharyngiomas can affect the hypothalamus, pituitary stalk, optic nerves and chiasm and carotid arteries. Compression of these neural and vascular structures frequently precipitates endocrine disorders, visual loss and an increased intracranial pressure. Hypopituitarism leading to a delayed puberty is a rare presentation of craniopharyngioma. The diagnosis of craniopharyngioma is usually made with the classic radiological imaging features based on CT and MRI. Copyright 2012 BMJ Publishing Group. All rights reserved.
Keywords: chorionic gonadotropin; gadolinium; growth hormone; testosterone; adolescent; article; case report; clinical feature; computer assisted tomography; contrast enhancement; craniopharyngioma; delayed puberty; follow up; headache; histopathology; human; hypopituitarism; male; nuclear magnetic resonance imaging; patient referral; priority journal; rare disease; short stature; signal detection; testosterone blood level; treatment outcome; tumor localization; tumor volume